PENGARUH PEMBERIAN GIBERELIN PADA MEDIA VACIN DAN WENT TERHADAP PERKECAMBAHAN BIJI ANGGERIK BULAN (Phalaenopsis amabilis Bl) SECARA IN VITRO - Yusnida Bey; Wan Syafii; Nur Ngafifah (Biogenesis, 2005)
In vitro investigation has conducted in order to find out the respons of orchid (Phalaenopsis amabilis BI) in Vacin and Went media by Gibberellins treatment, this research was carry out at Balai Benih Tanaman Pangan dan Holtikultura Pekanbaru during June until August 2003 by using completely Random Design through 5 treatment and 4 replication. The treatment were Gibberellins (ppm): 0, 2, 4, 6 and 8. The parameter were observed i.e ; the emergence timing of protocorm like bodies, seedling height, and seedling biomass. Observated data were analyzed descriptifely and analysis of variance with Duncan Multiple Range Test at 5% level of significance. The results shows that the 2 ppm GA3 treatment have a good effect on the emergence timing of protocorm like bodies (13-16 days after planting), average of seedling height (1,5 cm) and seedling biomass (1,18 gr). We concluded that the timing of orchid seedling emergence could be accelerated by increasing the concentration GA3 treatment until 2 ppm.     Key words:  Seed of orchid, Gibberellins,  In vitro, Germination, Phalaenopsis amabilis Bl